2022
DOI: 10.3390/agronomy12010152
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Leaf Chlorophyll Content Using High-Density SNP Array in Peanuts (Arachis hypogaea L.)

Abstract: The content of chlorophyll, a fundamental component required for photosynthesis in plants, has been widely studied across crop species. In this study, we aimed to evaluate the genetic diversity of 453 peanut accessions. We evaluated the evolutionary relationships using a genome-wide association study (GWAS) of leaf color data based on chlorophyll content analysis using the Axiom_Arachis array containing 58K single-nucleotide polymorphisms (SNPs). We identified seven SNPs as being significantly associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have successfully identified loci significantly associated with chlorophyll or anthocyanin in the leaves or petals of various plants, such as tea plant ( Camellia spp. Kamel) [ 23 ], peanut ( Arachis hypogaea L.) [ 24 ], rose ( Rosa rugosa Thunb.) [ 25 ], Gerbera hybrida [ 20 ], rice ( Oryza sativa L.) [ 26 , 27 , 28 ], and Perilla frutescens (L.) Britt.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have successfully identified loci significantly associated with chlorophyll or anthocyanin in the leaves or petals of various plants, such as tea plant ( Camellia spp. Kamel) [ 23 ], peanut ( Arachis hypogaea L.) [ 24 ], rose ( Rosa rugosa Thunb.) [ 25 ], Gerbera hybrida [ 20 ], rice ( Oryza sativa L.) [ 26 , 27 , 28 ], and Perilla frutescens (L.) Britt.…”
Section: Discussionmentioning
confidence: 99%
“…The gene Arahy. SDG4EV was found to be related to leaf chlorophyll content ( Zou et al, 2022 ). The chlorophyll content is a critical component affecting photosynthesis in plants and is associated with abiotic stress adaptation ( Singh and Thakur, 2018 ).…”
Section: Molecular Basis Of Stress Tolerancementioning
confidence: 99%
“…The development of high-density SNP chips in groundnut allowed the construction of high-density genetic maps that helped to saturate the large QTL intervals ( Pandey et al, 2017b ). SNP arrays were successfully used to dissect the yield-related traits ( Pandey et al, 2020b ), root-knot nematode resistance ( Ballén-Taborda et al, 2019 ), stem rot resistance ( Luo et al, 2020 ), late leaf spot resistance ( Han et al, 2018 ; Chu et al, 2019 ; Zhang et al, 2020 ), fresh seed dormancy ( Wang et al, 2022 ), leaf chlorophyll content ( Zou et al, 2022 ), salinity tolerance ( Zou et al, 2020a ), background genome recovery during a marker-assisted backcross selection in groundnut ( Shasidhar et al, 2020 ), and germplasm diversity analysis ( Nabi et al, 2021 ). Specific locus amplified fragment sequencing (SLAF-seq)-based high-density genetic map and phenotyping under multiple environments identified a total of 27 QTLs for seed weight, seed length, and width ( Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%